Heat Integration Strategies for Acetaldehyde Production: Optimizing Ethanol Dehydrogenation and Hydrogen Recovery - Faruq Naufal Yusuf; Muhammad Abiyyu Biantoro; Muhammad Faishal Mujahid; Hafidz Azwar Rahim; Elleonora Pramusita Prawira (UPT Laboratorium Terpadu, Universitas Diponegoro, 2025)
Acetaldehyde production via ethanol dehydrogenation is inherently energy-intensive due to its endothermic characteristics, while the hydrogen generated as a co-product must achieve high purity to meet industrial specifications. Enhancing energy efficiency and hydrogen quality is therefore essential to advancing the sustainability and economic feasibility of this process. This study investigates strategies to optimize energy consumption and hydrogen purity in acetaldehyde production through systematic heat integration and absorber operating condition optimization. Process simulations were employed to quantify the influence of internal heat exchanger integration on overall heat demand and to examine the effect of absorbent flow rate variation on hydrogen purification performance. Integration of heat exchangers reduced total energy consumption by